Effect of Water Temperature and Improper Storage on the Setting Time of Alginate Impression Material - Oky Laksa Indra Kencana, - (2021)
Background: Alginate is an irreversible hydrocolloid printed material containing various materials such as potassium alginate, calcium sulfate, sodium phosphate, potassium titanium fluoride, zinc oxide, and diatomaceous earth as filler. Purpose: The aim of this study was to know the effect of water temperature and improper storage on the setting time of alginate print material. Methods: This study consisted of 4 treatment groups, using Tulip brand alginate impression material (Cavex-Holland) exp 2018-04 and tap water. The time setting data were analyzed by One-Way ANOVA test and continued with Least Significant Different test (LSD). Results: A one-way ANOVA test was used to discover the significant differences between the four treatment groups. LSD test results show that there are significant differences between K-1 and other groups. Conclusions:that higher water temperatures and improper conditions in alginate printing material storage will accelerate the setting time.